Beyond the “Talking Cure”: The Practical Joke as Testimony for Intergenerational Trauma in Eden Robinson’s “Queen of the North” - Visvis, Vikki (Studies in Canadian Literature, 2004)
Literary critics, psychologists, and psychoanalists have recently taken up the question of whether narrativizing traumatic events can serve to transform pathogenic memories into accessible, articulate renderings, or speech acts that engender relief in those suffering from post-traumatic stress disorder. Some hold that the "talking cure," coined by Freud and Breuer, demands a vocabulary and syntax in some sense incommensurable with what went before it. Eden Robinson's text asks how one deals with trauma when the "talking cure" is not a viable healing stratagem. In "Queen of the North," the absence of a suitable addressee forces Adelaine to look for an alternative outlet for her traumatic experience. Adelaine's use of the practical or tangential joke, while ultimately ineffectual as a remedy for trauma, enables Robinson to avoid reducing the complexities of trauma and its cures.